Key topics in otolaryngology - Roland, N. J.; McRae, R. D. R. (Robert Duncan Roderick); McCombe, A. W. (Andrew Wightman) (Thieme, 2019)
The long and eagerly awaited third edition of this popular and compact textbook is here. Often labelled an ""exam bible"" in its previous editions, Key Topics in Otorhinolaryngology provides a concise yet comprehensive overview that clinical students and trainees alike can use. It will serve as an ideal introduction to ENT and also prove to be a valuable revision aid for ENT examinations. Conceived and edited by three very knowledgeable and highly respected ENT surgeonsfrom the UK with a wealth of examining experience and an in-depth understanding of the British, European, and International ex.